Filtered and unfiltered lipoaspirates reveal novel molecular insights and therapeutic potential for osteoarthritis treatment: a preclinical in vitro study - Behn, Alissa; Brendle, Saskia; Ehrnsperger, Marianne; Zborilova, Magdalena; Grupp, Thomas M.; Grifka, Joachim; Schäfer, Nicole; Grässel, Susanne (Frontiers in Cell and Developmental Biology, 2025)
IntroductionOrthobiologics, such as autologous nanofat, are emerging as a potential treatment option for osteoarthritis (OA), a common degenerative joint causing pain and disability in the elderly. Nanofat, a minimally processed human fat graft rich in stromal vascular fraction (SVF) secretory factors, has shown promise in relieving pain. This study aimed to elucidate the molecular mechanisms underlying nanofat treatment of OA-affected cells and compare two filtration systems used for nanofat preparation.MethodsChondrocytes and synoviocytes were isolated from articular cartilage and synovium of 22 OA-patients. Lipoaspirates from 13 OA-patients were emulsified using the Adinizer® or Lipocube™ Nano filter systems to generate nanofat. The fluid phase of SVF from both filtered and unfiltered lipoaspirates was applied to OA-affected cells. Luminex multiplex ELISA were performed with lipoaspirates and cell supernatants alongside functional assays evaluating cell migration, proliferation, metabolic activity, and senescence.ResultsA total of 62 cytokines, chemokines, growth factors, neuropeptides, matrix-degrading enzymes, and complement components were identified in lipoaspirates. Among these, significant concentration differences were observed for TIMP-2, TGF-ß3, and complement component C3 between the filtered and unfiltered samples. Nanofat enhanced chondrocyte proliferation and migration, as well as synoviocyte migration and metabolic activity, while reducing chondrocyte metabolic activity. Pain-related factors like β-NGF, MCP-1, Substance P, VEGF, and αCGRP were reduced, while anti-inflammatory TGF-β1+3 increased and pro-inflammatory cytokines (IL-5, IL-7, IL-15, and IFN-γ) decreased. Nanofat also elevated secretion of complement components and TIMPs in both cell types. Notably, our results revealed no significant differences in cellular effects between sSVF filtered using the Adinizer® and Lipocube™ Nano systems, as well as compared to unfiltered sSVF.DiscussionHere, we provide first insights into how autologous nanofat therapy may ameliorate OA by enhancing chondrocyte proliferation and synoviocyte migration while modulating inflammatory and pain-related factors. However, further research is needed to determine its effects on cartilage regeneration.